A candidate gene sequence for downy mildew resistance in Maize - Galvez, Hayde F.; Tongson, Eden Jane U.; Ripalda, Roanne R.; Canama, Alma O.; Malijan, Arma Kristal B.; Hautea, Desiree M. (2011)
We report a putative resistance gene ortholog for resistance to downy mildew caused by Peronosclerospora philippinensisWeston (shaw) in Philippine maize. We designed two gene-specific markers based on sequence information of the resistance gene analog, srga3. BLAST analysis of the srga3 amplicon showed 39 hits against the maize rust resistance protein rp3-1 gene with a maximum score of 81.3 and 78% identity. The gene-specific markers were tested for co-segregation with the srga3-quantitative trait loci (QTL) and downy mildew resistance phenotype on Bc1F1 mapping population consisting of 121 individuals. These will be used in map-based isolation of the downy mildew resistance gene in maize and marker-assisted selection towards the development of downy mildew resistant maize varieties.
Keywords: Maize; Downy mildew diseases; Disease and pest resistance